SISTEM DATA TERINTEGRASI TERINTERKONEKSI UNTUK DATA PILAH GENDER DI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Rahmi Syahriza; Nasrillah -; Nurasiah - (Journal of Gender and Social Inclusion in Muslim Societies, 2020)
The decree of Ministry of Education no. 84/2008, which set forth gender mainstreaming in educational field, brings to the consequence for executing the Gender Responsive Based Planning and Financing Management (GRPF). Meanwhile, this management of GRPF is only possible if the differentiated data gender is provided. This research is directed to know the policy and the statute of UIN-SU on the gender mainstreaming in the teaching-learning system and the institution management. Also, to know the steps and technological infrastructure needed in order that UIN-SU can create the gender data which is integral and interconnected. This research is a qualitative one and will conduct the PAR method. The findings of the research, among others, are First; the policy and the statute of UIN Sumatera Utara has not specifically mentioned about gender perspective and gender mainstreaming. Secondly; To create a system of gender data differentiation, some steps are needed to be done, i.e.; early observation and survey on the condition of gender data differentiation within the faculties and related units; socializing and discussing the result of the survey to the head and the decision maker in order to formulate the problem; Thirdly, The necessity to create the data gender differentiation in UIN-SU which should be coordinating with and handed in to the volunteer as well as IT experts (in this case PUSTIPADA UIN-SU). The execution of the data gender providing will be another step and being part of follow up in a research with PAR m ethod. The steps that the IT team did are; 1). Workshop for creating software of data gender differentiation; 2). Processing the existing system which is integral and connected to all faculties and office unit; 3). Producing regulation of the using and utilizing the systems.